Efficacy of switching to dolutegravir plus rilpivirine, the small-tablet regimen, in patients with dysphagia: two case reports - Takefumi Suzuki; Nobuko Hara; Morichika Osa; Kazuhisa Misawa; Kazuo Imai; Yuji Fujikura; Takuya Maeda; Wataru Sonehara; Akihiko Kawana (BMC, 2017)
Abstract Background The advent of well-tolerated and effective anti-retroviral drugs against human immunodeficiency virus-1 (HIV-1) infection has been a major step forward that has achieved long-term survival in recent years. The number of HIV-1 infected patients who experience difficulty in swallowing tablets is expected to increase as the HIV-infected population advances in age or develops comorbidities or treatment sequelae affecting the central nervous system. Case presentation Here, we describe two HIV-1-infected patients who experienced progressive dysphagia leading to inability to swallow the antiretroviral tablets included in the standard regimen. Both patients had a plasma viral load < 40 copies/mL while receiving anti-retroviral therapy with the recommended combination antiretroviral therapy (cART) regimen, but the dysphagia necessitated a switch. By switching to much smaller sized combined regimen of dolutegravir (DTG) plus rilpivirine (RPV) tablets, both of our patients were able to successfully continue treatment and maintain adherence without the need for crushing tablets or preparing an oral suspension. Additionally, switching from the recommended cART regimen to DTG plus RPV successfully maintained viral suppression. At the last available follow-up (12 months after switching to DTG/RPV), HIV-1 viral load remained below the lower limit of quantification. Conclusions An alternative therapeutic option that takes tablet size into consideration could not only contribute to improved patient adherence, but also a reduced care burden for HIV-infected patients with dysphagia. Thus, switching to the "small-tablet regimen" of DTG plus RPV has the potential to improve the survival and well-being of patients with dysphagia.